STRATEGY OF E-TOURISM USE TO PROMOTE KAMPUNG NAGA, TASIKMALAYA, WEST JAVA, INDONESIA - Maya Dora, Yenny; Farhi Saudi, Hammad; Saudi, Madihah (International Journal of Psychosocial Rehabilitation, 2020)
Kampung Naga is one of the tourist villages based on cultural customs or local wisdom. It is one of the village communities in Indonesia. The village is still preserving the cultural customs that are located in Neglasari Village, Salawu Sub District, Tasikmalaya District. The people still hold strong the traditions that are inherited from their ancestors. Kampung Naga is also still a community either its beliefs or culture that is not affected with the cultures outside their village. And they also still exist and are still able to survive in the midst of cultural changes that occur in West Java in particular and Indonesian society in general. This research is to develop a strategy of using e-tourism to promote Kampung Naga as a tourist destination which is worth visiting by tourists, especially cultural-loving tourists. The analysis technique is the SWOT analysis. The research results can be used by related parties to develop and improve tourism in Kampung Naga.